Implementation of GCG (Good Corporate Governance) on the Prevention of Fraud Financing in Islamic Banks - Cholisoh, Lies; Hadziq, M. Fuad (El-Qish: Journal of Islamic Economics, 2021)
Although Islamic Banking operates with Islamic principles, there are still many frauds that are committed deliberately for particular cases. This study aims to determine the extent of the influence of Good Corporate Governance in Islamic banking on indications of fraud, especially at Bank BNI Syariah. This research is quantitative research with primary and secondary data, namely using a sample questionnaire and interviews. While the data analysis is using multiple regression with descriptive analysis. The results of the study concluded that the resulting regression had a very small R square at 34.7%. Finding. The results of the t-test show that partially the independent variables in GCG, namely information disclosure, accountability, responsibility, independence, fairness, are stated to not affect the financing of fraud. This is because the number of R squares has a small effect. After all, it is below 50% so that the impact on the insignificance of the variables in GCG on fraud financing. Therefore, it results from the t-test in which none of the X variables affect variable Y. From the information above, it can be concluded that the GCG variable simultaneously has a significant effect on financing fraud, but if tested partially, the GCG variable has no effect on financing fraud.